Perceptions Of The Effectiveness Of Sports Health Programs In Improving Adolescent Fitness In The Community - Aqilah Nasution; Dinda Rezqia Maharani; Zahla Fauzia; Muhammad Arief Setiawan (COMPETITOR: Jurnal Pendidikan Kepelatihan Olahraga, 2024)
This research, which uses approach descriptive quantitative method survey, successfully describes the perception of a teenager of the effectiveness of sports health programs in improving fitness and their physical and mental health in society. Previous research shows that more active teenagers in a way physique tend to own ability concentration and power to remember better and be more persistent under pressure academic and social. The total sampling consisted of 19 respondents teenagers, and data was collected through a questionnaire containing questions open and closed which included various aspects of sports participation. Results of the analysis show that the majority of teenagers (94.7%) agree that sports contribute to improving performance academic, which indicates the existence connection between physical activity and functional cognitive support educational achievement. Sense of trust in self (89.5%), power body resistance (100%), as well as help to form habit life healthy (100%). Support for family and society is also considered important (94.7%), while sports facilities are assessed as Still not adequate by most big respondents (57.9%).